Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Model Discovery Learning Pada Materi Laju Reaksi - Valentina, Ni Luh Gaoura Astari; Al Idrus, Syarifa Wahidah; Junaidi, Eka (FKIP University of Mataram, 2025)
This study aims to develop a student worksheet based on the Discovery Learning model for the reaction rate topic and to determine its feasibility in terms of validity through expert validation. The development model used is the 4D model, which consists of four stages: define, design, develop, and disseminate. However, this research is limited to the development stage, focusing on the feasibility testing of the student worksheet. The trial was conducted with 40 students at SMAN 2 Mataram. The research instruments included interview sheets and validation sheets for student worksheets. The data collected comprised both quantitative data, in the form of scores from expert validators using the validation sheets, and qualitative data, in the form of suggestions and feedback from validators. The validation sheets used a Likert scale. The validation results showed a score of 89.63% for the content/material aspect, 95.56% for presentation, 90.00% for language, and 91.63% for graphic feasibility. The overall average score for all aspects of the LKPD was 91.63%, with a reliability score of 94.00%, indicating that the student worksheet is highly feasible and suitable for use in the learning process.